Riboswitches in Archaea - Gupta, Angela; Swati, D. (Combinatorial Chemistry & High Throughput Screening, 2019)
Background: Riboswitches are cis-acting, non-coding RNA elements found in the 5’UTR of bacterial mRNA and 3’ UTR of eukaryotic mRNA, that fold in a complex manner to act as receptors for specific metabolites hence altering their conformation in response to the change in concentrations of a ligand or metabolite. Riboswitches function as gene regulators in numerous bacteria, archaea, fungi, algae and plants. Aim and Objective: This study identifies different classes of riboswitches in the Archaeal domain of life. Previous studies have suggested that riboswitches carry a conserved aptameric domain in different domains of life. Since Archaea are considered to be the most idiosyncratic organisms it was interesting to look for the conservation pattern of riboswitches in these obviously strange microorganisms. Materials and Methods: Completely sequenced Archaeal Genomes present in the NCBI repository were used for studying riboswitches and other ncRNAs. The sequence files in FASTA format were downloaded from NCBI Genome database and information related to these genomes was retrieved from GenBank. Three bioinformatics approaches were used namely, ab initio, consensus structure prediction and statistical model-based prediction for identifying riboswitches. Results: Archaeal genomes have a sporadic distribution of putative riboswitches like the TPP, FMN, Guanidine, Lysine and c-di-AMP riboswitches, which are known to occur in bacteria. Also, a class of riboswitch sensing c-di-GMP, a second messenger, has been identified in a few Archaeal organisms. Conclusion: This study clearly reveals that bioinformatics methods are likely to play a major role in identifying conserved riboswitches and in establishing how widespread these classes are in all domains of life, even though the final confirmation may come from wet lab methods.
Keywords: aptamer